KAJIAN KOMPOSISI BAHAN ORGANIK SEBAGAI NUTRISI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza Sativa L.) VARIETAS CIHERANG - Firman, Yaumul; Sulistiyo Budi, Luluk; Rahayu, Sri; Lukito, Martin (JURNAL AGRI-TEK, 2017)
The declining quality of the environment that has the effect of reducing national rice productivity. Required cultivation techniques where the production of rice crops remain qualified, attention to the health and soil fertility and maintain the environment that is by using organic materials that are easy to find around the environment. Like leaf lamtoro plant, blotong, azolla plant, pure manure, molasses and utilization of microorganisms. The aim of this research is to study the response of organic composition as nutrient to growth and yield of rice crop (Oryza sativa L.) Ciherang Variety. The method of research was used Completely Randomized Design of one factor with three replications. Implementation of research using media polybag so get 72 polybag on each replication. Each replication is multiplied by three to 216 polybags, the distance between polybags is 25 cm. The results of the composition of organic matter showed the highest value on the treatment (Urea, SP36 and KCl) in all variables. The average number of tillers and the number of panicles showed higher yields on the average number of pith (%) and the lowest number of seeds (%). Some of the above variables show the study of the composition of organic materials as nutrients to growth and yield of rice crop (Oryza sativa L.) Ciherang Variety. Keywords: Nutrition, Organic Fertilizer, Growth and yield of Rice Plant